A RARE CASE REPORT OF SUBDURAL HAEMATOMA WITH ANEMIA APLASTIC - Feda Anisah Makkiyah; Rahmah Hida Nurrizka (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2021)
This article illustrates the development of a rare case of spontaneous subdural hematoma (SDH) secondary to aplastic anemia and conservative treatment of SDH. Clinical Presentation: a 43-year-old male complained of severe progressive headaches that starting from one month ago. His laboratory values showed pancytopenia and his peripheral blood smear showed no abnormalities except for the lack of number of erythrocytes, leukocyte, and thrombocyte. We could not find any malignancy in the smear. The patient experienced progressive headache, disorder of balance, and decrease of consciousness. CT imaging of the head showed a 7.0 cm (2 cm thickness) left frontal-parietal subdural hematoma. Patient were managed conservatively. This is a rare case of aplastic anemia with subdural hematoma and the patient was discharged in good condition.